Review of the Fund's Transparency Policy. (Policy Papers; Policy Paper, 2009)
The Fund has come a long way since the inception of its policy toward increased openness some ten years ago. Most Board documents are now published; the volume of information in the Fund's archives has increased significantly; and the Fund has strengthened outreach efforts to explain its operations and views to the outside world. Transparency and openness has become increasingly seen as a normal and essential part of the Fund's business. There are significant benefits from increased transparency: it strengthens the Fund's ability to influence public debate, subjects the Fund to outside scrutiny, and enhances the Fund's legitimacy by making it more accountable. These benefits will only loom larger as the Fund takes on a larger role in calling out risks to the global economy, to help prevent future economic and financial crises. Indeed, in today's world openness from public institutions like the Fund is generally expected.